2005
DOI: 10.1051/0004-6361:20052847
|View full text |Cite
|
Sign up to set email alerts
|

Energy levels and radiative rates for transitions in Ar XIII, Ar XIV and Ar XV

Abstract: Abstract. Energies for 524 levels of Ar XIII, 460 levels of Ar XIV and 156 levels of Ar XV have been calculated using the  code of Dyall et al. (1989). Additionally, radiative rates, oscillator strengths, and line strengths are calculated for all electric dipole (E1), magnetic dipole (M1), electric quadrupole (E2), and magnetic quadrupole (M2) transitions among these levels. Comparisons are made with the limited results available in the literature, and the accuracy of the data is assessed. Our energy leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
(43 reference statements)
9
21
1
Order By: Relevance
“…the level order 19 and 20 are exchanged in our FAC1 and FAC2 results. Similar results were found by Aggarwal et al (2005). We note that the level ordering of FAC2 is consistent with those listed in the NIST database.…”
Section: Energy Levels and Wavelengthssupporting
confidence: 88%
See 1 more Smart Citation
“…the level order 19 and 20 are exchanged in our FAC1 and FAC2 results. Similar results were found by Aggarwal et al (2005). We note that the level ordering of FAC2 is consistent with those listed in the NIST database.…”
Section: Energy Levels and Wavelengthssupporting
confidence: 88%
“…We note that discrepancies of several magnitudes are found for a few weak transitions. Aggarwal et al (2005) suggested that this differences can be attributed to the different configurations involved in different calculations. Apart from this, strong level mixing and the different methods adopted in the calculations may also cause large differences (Liang et al 2009).…”
Section: Radiative Ratesmentioning
confidence: 99%
“…For Ar 13+ , a grasp calculation is available, which included the 2s x 2p y (x + y = 3), 2s 2 {3, 4, 5}l, 2s2p{3, 4, 5}l, 2p 2 {3, 4, 5}l (l < f ), and 2s 2 {6, 7, 8}s configurations (Aggarwal et al 2005). Notes.…”
Section: Structure: Level Energiesmentioning
confidence: 99%
“…For Ar 13+ , the 460-level grasp calculation performed by Aggarwal et al (2005) is the largest-scale work for this ion to our best knowledge. We provide a comparison with their results, again in Fig.…”
Section: Structure: Line Strength Smentioning
confidence: 99%
“…Some calculations were performed for selected individual ions (Kramida & Träbert 1995;Tully & Chidichimo 2001Chidichimo et al 2003;Aggarwal et al 2005;Chidichimo et al 2005;Landi & Gu 2006;Savukov & Markhotok 2006;Bhatia & Landi 2007a, 2007bGu 2007;Duan et al 2008;Del Zanna et al 2008;, 2009a, 2009bHudson 2009;Mania et al 2009;Aggarwal & Keenan 2014). However, a majority of these calculations are at the level of a relatively simple configuration interaction method, which implies a relatively lower accuracy.…”
Section: Introductionmentioning
confidence: 99%